Simulation-based investigation of the metrological interface structural resolution capability of X-ray computed tomography scanners - Busch, Matthias; Hausotte, Tino (Journal of Sensors and Sensor Systems, 2023)
In the course of the miniaturization of components, new demands are also being placed on the measuring systems intended for component inspection. In this context, the resolution of a measuring system is often of interest. As a volumetric analysis method and method of non-destructive testing, the industrial X-ray computed tomography (XCT) has the ability to measure dimensions and geometry inside a component without destroying it and can therefore be used for quality assurance. However, the concept of resolution is not trivial for XCT and has not yet been finally clarified, especially for the detectability of two surfaces facing each other. Therefore, this article describes a procedure for investigating this type of resolution with the use of a test specimen. The test specimen contains several radially arranged holes of the same size, the diameters of which also correspond to the distance between the holes to investigate the resolvability of surfaces and interfaces. The evaluation is based on mean and extreme values of grey value profiles between the individual boreholes of the reconstructed volume. The investigations are based on XCT simulations. It is shown that the detectability of the metrological surface and interface can be extended by a reasonable choice of the threshold value for surface definition within a defined interva